2000
DOI: 10.1179/135100000101535348
|View full text |Cite
|
Sign up to set email alerts
|

New developments in the analysis of gene expression

Abstract: An understanding of the relationship between gene expression, protein expression and the influences of genetic responses upon gene function is vital before we can understand the complexity of genomes. Traditional methods for the study of gene expression are limited to studying small groups of genes at a time and a source of pure starting material has been difficult to obtain. Recent technological advances have enabled large numbers of genes, from specific cell populations, to be studied in a single experiment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…2a). These results are in agreement with previous reports which had demonstrated similar sensitivity for cellular gene detection in microdissected cells [35,41].…”
Section: Hcv Rna Quantification From Microdissected Cellssupporting
confidence: 95%
“…2a). These results are in agreement with previous reports which had demonstrated similar sensitivity for cellular gene detection in microdissected cells [35,41].…”
Section: Hcv Rna Quantification From Microdissected Cellssupporting
confidence: 95%
“…These results suggested that decreased expression of the synaptic proteins might lead to the reduction of neurotransmitter release, and therefore contributed to the impairment of synaptic plasticity and cognitive functions in AD and aging. On the other hand, several technical issues concerning the complexity of neuron cell types and the post-mortem changes need to be addressed carefully in the future experiments [32][33][34].…”
Section: Genes Associated With Alzheimer's Dis-ease and The Brain Agingmentioning
confidence: 99%
“…Many analysis methods and algorithms have been developed for the analysis of the gene expression matrix [1,2,3,4,5,6,7,8,9]. The clustering of genes for finding coregulated and functionally related groups is particularly interesting in cases where there is a complete set of organism's genes.…”
Section: Introductionmentioning
confidence: 99%